Spatial distribution of the ethnomedicinal plant Aglaonema simplex at the Sakaerat Environmental Research Station, Northeastern Thailand - NUTCHAPAT O-THONG; WATTANACHAI TASEN; DOKRAK MAROD; SATHID THINKAMPHEANG; WONGSATORN PHUMPHUANG (Society for Indonesian Biodiversity, 2024)
Abstract. O-thong N, Tasen W, Marod D, Thinkampheang S, Phumphuang W. 2024. Spatial distribution of the ethnomedicinal plant Aglaonema simplex at the Sakaerat Environmental Research Station, Northeastern Thailand. Biodiversitas 25: 3043-3050. Aglaonema simplex Blume (Araceae) is an evergreen herbaceous plant used ornamentally and in traditional medicine. Although the usefulness of this plant has been widely studied and reported, its ecology remains poorly understood. In this study, we examined the effects of various environmental factors on the spatial distribution of A. simplex in a Dry Evergreen Forest (DEF) at the Sakaerat Environmental Research Station (SERS) in Northeastern Thailand. All individual plants were counted; their positions were recorded within a 16-ha Forest Dynamics Plot (FDP), and their distribution pattern was analyzed using Ripley's K function. The spatial distribution of A. simplex was determined using a generalized linear model that incorporated plant density and topographic and edaphic variables within the 16-ha study plot. We found a total of 11,232 A. simplex individuals with a density of 702 individuals ha-1, with a clumped distribution pattern. The modeling results showed that the spatial distribution of A. simplex was positively influenced by soil clay content, soil pH, exchangeable magnesium, and adult tree density; it was negatively influenced by sapling density and rocky outcrops. These findings contribute to the broader understanding of the ecological niche of A. simplex. They can be used to design integrated land management approaches that balance ecological conservation with economic development goals.